San Miguel, patrono de Pallatanga y su influencia en la religión en los habitantes entre los años 1966-1970 - López Gaibor, Hilda Jiseña (2016)
The research deals with “San Miguel de Pallatanga” and his influence on the religious life of inhabitants in the province of Chimborazo from 1966 to 1970. Religion has its roots in the Roman Empire, where religion was the opium of the people; with the arrival of the conquering Spaniards and Portuguese in Latin America, they introduced this tradition in all the pre-colombinos people as part of the culture. In Ecuador, some religious brotherhoods arrived such as: Jesuits, Franciscans, Augustinians, Dominicans; the only religion recognized and approved by Ecuador from the republican life to the present time was the Roman Catholic in the constriction held in Riobamba city in 1830. Thus, in Ecuador in 1966 other religious sects began to proliferate specifically in rural areas due to the total neglect of the church; we sought through the theology of liberation waged by religious to vindicate servants; This is the case of Pallatanga located in Chimborazo, the inhabitants of this sector, migrants and indigenous people have embraced these new congregations in their way of life. In 2015, it can be noted a total apathy and a division among these people; for example, this year there were no processions in honor to “San Miguel de Pallatanga”.